Policing partnerships to address youth antisocial behavior: How parental risk-taking shapes child outcomes - Mazerolle, Lorraine (Criminology & public policy, 2020)
Research Partnerships are an integral part of the working life of police, yet not a lot is known about how such partnerships work to deter and control crime problems. This article explores the impact of a Third Party Policing Partnership involving police and schools coming together to engage with parents to address their child's truancy and antisocial behavior. We report on results from an embedded behavioral economics experiment within the Ability School Engagement Program (ASEP) Trial. ASEP involved 102 young people who were chronically truant from school and randomly allocated to the experimental partnership program (ASEP) or the business-as-usual condition. We find that riskier choices made by parents increase the incidence of child self-reported antisocial behavior (SRASB). Our results show parents in the ASEP condition had greater gains in knowledge of the education laws relative to control. There was a backfire effect for parents in the control group: Their gains in knowledge of the laws led their children to have higher levels of SRASB. Policy Implications Policing partnerships are an important part of the future of policing. Police partnerships with schools are a promising approach for engaging parents and young people in a manner that clearly and fairly explains to parents their legal obligations for their child's school attendance. While we do not find that ASEP modified parental risk-taking behavior, we do find that the ASEP intervention created an insulating effect from the negative outcomes of the business-as-usual condition, in which school principals delivered ad hoc bad news to parents about their child's antisocial behavior in a way that was not procedurally just. Policing partnerships are likely to deter antisocial behavior when police work with third party partners who have some type of legislative responsibility. This legislative medium creates opportunities for the police and third parties to better engage and communicate legal responsibilities and the consequences of noncompliance.